Computer aided learning Chinese Iiioms ( CALCI) / Yee Chai Yam - Yee, Chai Yam (2001)
Computer aided learning have been implemented by lots of institutions and universities nowadays, due to the fast growing of information technology and the trend of moving towards paperless environment. Computer aided learning of Chinese idioms, is a package developed to assist students in the Chinese idioms study. This package is limited to Chinese idioms in 4 characters only. The package will provides the entire syllabus of Chinese idioms learned at primary and secondary school. It also contains idioms story, exercises and quizzes. The development of this package is assisted by multimedia tool to make it a more attractive, efficient and effective during Learning process. It is hope that development of this package will assist all students to achieve better result in their examination.